Pendidikan Karakter: Sebuah Kajian Literatur - Bakhrudin All Habsy; Wulani Azka Shafiqoh Najwa; Adwinata Asafwa Putra; Amelia Fitri Nafidhatus Sholickha (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
Character education is a systematic effort that aims to shape an individuals personality holistically, including moral, ethical and noble values aspects that are important for social life. In its implementation, character education is integrated into various subjects, extracurricural activities, and the school environment that supports the creation of an educational atmosphere that encourages good character development. This research aims to investigate character value and the impact of character education as well as challenges in implementing character education using qualitative research methods, which use article review. Based on the method use to gain an understanding of character education material through journal sources, articles and also objects relevant to the research. The research results include: (1) Definition of character education, (2) Objectives of character education, (3) Benefits of character education, (4) Main values in character education, (5) Challenges in character education, (6) Methods of implementing education character, (7) Character education in the digital era.